If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5z = 3z + -4 Reorder the terms: 5z = -4 + 3z Solving 5z = -4 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. 5z + -3z = -4 + 3z + -3z Combine like terms: 5z + -3z = 2z 2z = -4 + 3z + -3z Combine like terms: 3z + -3z = 0 2z = -4 + 0 2z = -4 Divide each side by '2'. z = -2 Simplifying z = -2
| 8+x=28+x | | 9-c=2c | | W-10/-2=0 | | 4c-2=18 | | 2x+12=-3x+5 | | Y=9/8x | | 2(z+-13)=-12 | | 5xa-12xa=-35 | | X+8=28+X | | 4y+8=3y | | 6q+2r-q+7r= | | -9d-4d=15 | | 129+191=n | | 10h-5h-4=6 | | 5a-12a=-35 | | 3x(3x-2)-4x(3x+4)= | | 13x+26=6x+180 | | 8q-5q= | | 9c-8=1 | | 2x-x=24-2x | | 20d-18d=2 | | 9y-6=-456 | | 7g=4 | | 17d-15d=20 | | 4n-6=94 | | x/4=3/4 | | 5x(2x+3)-2x(2x-1)= | | 2x-1/5=1 | | h=-16t^2+60t+2 | | 3a+6b+2a-5b= | | 2/7(x-4)=2 | | 2.20=12.15 |